2017
DOI: 10.1186/s13071-017-2217-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dog owner adherence to veterinarians’ flea and tick prevention recommendations in the United States using a cross-sectional survey

Abstract: BackgroundAdherence to a prescribed therapeutic regimen is a critical factor for achieving medication effectiveness and therefore treatment success. In the case of companion animal ectoparasite control, suboptimal owner adherence to medication recommendations is thought to be a common cause of treatment failure, and previous reports have found pet owners applying an average of 4.0–4.6 monthly flea and tick treatments per year to their dogs. This study investigated: US veterinary hospital self-reported flea and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 18 publications
1
54
0
3
Order By: Relevance
“…While numerous parasite preventives are currently available for use in dogs, extensive protection against both ecto-and endoparasites usually requires multiple medications often with varying administration routes and directions [29]. Recent research in both the USA and Europe shows owner compliance in the prevention and treatment of internal and external parasites frequently falls short of expert recommendations [30][31][32][33][34]. Within the USA, 73% of dog owners in one survey believed their dog should receive year-round flea and tick preventives but only 13% actually purchased sufficient medication to achieve year-round protection [32], and owner compliance in the correct administration of canine heartworm preventive is documented as well below 100% [30,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous parasite preventives are currently available for use in dogs, extensive protection against both ecto-and endoparasites usually requires multiple medications often with varying administration routes and directions [29]. Recent research in both the USA and Europe shows owner compliance in the prevention and treatment of internal and external parasites frequently falls short of expert recommendations [30][31][32][33][34]. Within the USA, 73% of dog owners in one survey believed their dog should receive year-round flea and tick preventives but only 13% actually purchased sufficient medication to achieve year-round protection [32], and owner compliance in the correct administration of canine heartworm preventive is documented as well below 100% [30,35].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research in both the USA and Europe shows owner compliance in the prevention and treatment of internal and external parasites frequently falls short of expert recommendations [30][31][32][33][34]. Within the USA, 73% of dog owners in one survey believed their dog should receive year-round flea and tick preventives but only 13% actually purchased sufficient medication to achieve year-round protection [32], and owner compliance in the correct administration of canine heartworm preventive is documented as well below 100% [30,35]. The use of multiple medications may add further hurdles for owners; an analysis of clinic transaction records for 231,565 dogs receiving flea and tick medication showed approximately 66% of owners purchased insufficient protection to provide the veterinarian's recommended yearround protection [31].…”
Section: Discussionmentioning
confidence: 99%
“…Medication purchasing data are a reliable surrogate for medication adherence, 29 as long as the purchased medication is administered as recommended. Purchased medication may not be administered as recommended, which means adherence measured from medication purchases would then overestimate true adherence by an unknown amount.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies found that veterinarians in the United States recommend 12 months of protection each year against eas and ticks. 8,29 Cat owners increased their adherence to this recommendation through use of a product with a longer duration of action. This is also consistent with prior data showing that treatment adherence is inversely related to dosing frequency, a critical convenience factor.…”
Section: Discussionmentioning
confidence: 99%
“…Sie lässt sich nach einer Formel der American Animal Hospital Association wie folgt darstellen: Compliance = tierärztliche Empfehlung + Besitzerakzeptanz + Nachsorge durch Tierarzt und Praxisteam [12]. Die Mitarbeit des Besitzers ist also ausschlaggebend für den Behandlungserfolg [12][13] [14]. Wie gut sie letztendlich ausfällt, hängt allerdings nicht, wie häufig angenommen, allein vom Besitzer ab.…”
Section: Introductionunclassified